Brief Communication on Laser Treatment for Diabetic Retinopathy - Shokirova, Makhbubakhon (International Journal of Contemporary Sciences (IJCS), 2023)
Diabetic retinopathy is a growing global health issue affecting 5% of the global population. With over 60,000 new cases reported annually, over 1 million individuals with diabetes are at risk of lower limb amputation. Diabetic retinopathy is diagnosed in 20% of patients with diabetes mellitus. Factors contributing to its prevalence include modern technology, sedentary lifestyles, and poor adherence to healthy practices. This article examines the negative effects of diabetic retinopathy and the need for comprehensive measures to reduce its impact. It provides insights into managing diabetic retinopathy and its impact on global health systems through research and advancements in diagnostic and treatment methods